Heat transfer properties and molecular mechanisms of cuspidine (Ca4Si2O7F2): An atomic-scale molecular dynamics study. (18th May 2022) - Huang, Shuheng; Wang, Zhe; Wang, Fanmao; Liu, Feng; Barati, Mansoor
Highlights: Equilibrium molecular dynamics simulations were conducted to evaluate the thermal conductivity of cuspidine in the temperature range of 293 to 1673 K. The thermal conductivity of cuspidine decreases significantly from 14.3 to 3.4 W/m·K with increasing temperature. The phonon scattering is the main contributor to the reduced thermal conductivity of cuspidine at higher temperatures. Abstract: Cuspidine (Ca4 Si2 O7 F2 ) is often formed in the fluoride-contained sintering processes and has attracted increasing attention due to its critical effect on heat transfer phenomena involved in such processes. However, the heat transfer properties of cuspidine and its underlying molecular mechanisms remain unknown because of difficulties in preparing monocrystalline cuspidine. In the present work, equilibrium molecular dynamics simulations were conducted to evaluate the thermal conductivity of cuspidine below its melting temperature. The results showed that in the temperature range of 293 to 1673 K, the thermal conductivities of cuspidine showed a negative dependence on temperature and decreased from 14.3 to 3.4 W/m·K. Further, the results of vibration density of states and kinetic energy analysis suggest that phonon scattering is the main contributor to a reduced thermal conductivity of cuspidine at higher temperatures. The findings provide insight into the heat transfer properties of cuspidine and the underlying molecular mechanisms.